Pengaruh Metode Pembelajaran Berbasis Proyek terhadap Kemampuan Kognitif pada Anak Kelompok A di RA Al-Aziziyah Desa Parakan Manggu Parigi Pangandaran - Elis Stiawati; Ida Kurniasih (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
Project-based methods are learning methods that can be applied to all levels ofeducation. The learning model begins with the stage of collecting information in the form of ideas and questions from children according to the chosen topic and then developed into learning and exploration activities. Learning using project-based methods students develop a project either individually or in groups to produce a product. The topics in the project approach must be concrete, close to the child's personal experience, interesting, have emotional and intellectual potential related to everyday life so that children can be active and creative in solving problems. This study aims to determine the effect of project-based learning methods on cognitive abilities and cooperation in children at RA Al-aziziyah Parakanmanggu, Parigi District. The population in this study were all children of the A Ra Al-aziziyah group, Dukuh Satu, Parigi District, for the 2021/2022 Academic Year. The sample in this study were all children of the A Ra al-aziziyah group, which amounted to 15 people. Among them 4 girls and 11 boys. The data collection method used in this study is the observation method where researchers go directly to the field to uncover and explore the use of project-based methods, namely making the shape of the sun using natural materials on the theme ofthe universe that is used by teachers to improve cognitive abilities and cooperation in early childhood. The results showed that with 1) good cooperation and preparation between children and teachers during learning activities to make the shape of the sun 2) collecting natural materials, namely leavesfrom the schoolyard, 3) making shapes rather difficult and sticking dry leaves on HVS paper, and 4) skilled in making the shape of the sun can increase creativity, so the children of RA Al-aziziyah Parakanmanggu Parigi Pangandaran experienced an increase which was categorized as good in listening to explanations about project-based methods.